Physical Activity in Puberty Is Associated with Total Body and Femoral Neck Bone Mineral Characteristics in Males at 18 Years of Age - Tamme, Reeli (Medicina (Kaunas), 2019)
Background and objectives: Studies indicate that genetic and lifestyle factors influence optimal bone development. Adaptations in bone mineral characteristics related to physical activity (PA) are most often observed in pre- and peri-puberty. Longitudinal associations between bone mineral accrual and objectively measured PA in puberty are poorly understood. The present study aims to investigate whether pubertal PA at different intensities is related to bone mineral characteristics in individuals at 18 years of age. Materials and Methods: Anthropometrics, pubertal stage, bone age and PA by accelerometer were measured in 88 boys at the mean age of 12.1 (T1), 13.1 (T2), 14.0 (T3) and 18.0 years (T4). Different bone mineral parameters were measured by dual-energy X-ray at T4. Stepwise multiple regression analysis was performed to determine the effect of bone age, body mass and PA characteristics on measured bone mineral parameters at 18 years of age. Results: Total PA in puberty together with mean pubertal body mass predicted 35.5% of total body (TB) bone mineral density (BMD), 43.0% of TB less head (LH) bone mineral content (BMC) and 48.1% of BMC/height in individuals at 18 years of age. Vigorous PA and body mass in puberty predicted 43.2% of femoral neck (FN) BMD; bone age at T1, vigorous PA and body mass in puberty predicted 47.3% of FN BMC at 18 years of age. No associations between pubertal PA levels and lumbar spine bone mineral characteristics in individuals at 18 years of age were found. Conclusions: Physical activity in puberty has a significant impact on bone mineral characteristics in individuals at 18 years of age, with total PA being a significant predictor of TB BMD and TB LH BMC as well as BMC/height, whereas vigorous PA is a significant predictor of FN BMD and FN BMC.